The Maqāṣid al-Qur’ān Approach According to ʿAbd al-Karīm al-Ḥamīdī: Implications for Qur’anic Exegesis - Adida, Nusratin; Nurul Fauziah Ramdlani (Journal of Ulumul Qur'an and Tafsir Studies, 2025)
Discusses the contribution of ʿAbd al-Karīm al-Ḥamīdī, an Algerian scholar born in 1958, in developing the concept of maqāṣid al-Qur'ān. Through his academic background in fiqh and ushul fiqh, al-Ḥamīdī emphasizes that the Quran is not just a book of law, but a revelation that contains noble values and main goals (maqāṣid) that must be realized in human life. In his work, al-Ḥamīdī divides the maqāṣid of the Quran into three categories: general maqāṣid (al-maqāṣid al-'āmmah), specific maqāṣid (al-maqāṣid al-khāṣṣah), and partial maqāṣid (al-maqāṣid al-juz'iyyah). This division aims to facilitate understanding of the objectives of the Qur'an, both in terms of breadth and detail. He also emphasizes that the maqāṣid of the Quran is in line with the maqāṣid al-sharī'ah, which is to protect the five fundamental aspects of life: religion, soul, mind, offspring, and property. al-Ḥamīdī's approach to maqāṣid al-Qur'ān makes an important contribution to understanding and developing Islamic law in a more dynamic and contextual manner. He encourages an understanding of Islamic law that does not solely rely on the literal text (nash), but also pays attention to the purpose behind the enactment of the law. Thus, Islamic law can appear more flexible and relevant to the dynamics of the times, and be able to answer various contemporary issues such as human rights, social justice, environmental preservation, and modern technological advances. Through his works, ʿAbd al-Karīm al-Ḥamīdī has made a significant contribution to the understanding and development of Islamic thought, especially in the context of maqāṣid al-Qur'ān. This approach is an important foundation in shaping Islamic law that is relevant, open, and in favor of universal human values.